The influence of crate height on selected biochemical indices in captive-reared mallards - Bedanova, Iveta; Voslarova, Eva; Chloupek, Jan; Pistekova, Vladimira; Forejtek, Pavel; Passantino, Annamaria (Animal science journal, 2014)
The aim of this study was to investigate the effects of crate type (particularly its height) on selected biochemical indices in captive-reared mallards (Anas platyrhynchos). The physiological changes in response to 2-h crating in crates of either 20 cm or 26 cm height were monitored in 6-week-old mallards. Plasma corticosterone concentrations showed an increase (P = 0.036) in mallards crated in crates of 26 cm height in comparison with control non-crated birds, whereas no difference in plasma corticosterone levels was found between mallards crated in crates of 20 cm height and control non-crated birds. Lower concentrations of plasma triglycerides (P < 0.05) and uric acid (P < 0.05) were found in crated mallards in comparison with control non-crated birds; the height of the crates had no effect. Mallards crated in crates of 26 cm height also exhibited a higher (P = 0.032) plasma lactate dehydrogenase concentration in comparison with control non-crated birds, whereas no difference (P > 0.05) was found in lactate dehydrogenase concentrations in mallards crated in crates of 20 cm height. Our results suggest that crating mallards in lower crates (20 cm) may be less stressful than keeping them in crates allowing vertical movements of the birds.
Keywords: zvířata; Animals; doprava; Housing, Animal; laktátdehydrogenasy; kachny; bydlení zvířat; Transportation; kortikosteron; Uric Acid; kyselina močová; Corticosterone; Triglycerides; Ducks; triglyceridy; Lactate Dehydrogenases